2020
DOI: 10.2196/preprints.18759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technology-Enabled Solutions for Australian Mental Health Services Reform: Impact Evaluation (Preprint)

Abstract: BACKGROUND Health information technologies (HITs) are becoming increasingly recognised for their potential to provide innovative solutions to improve the delivery of mental health services and drive system reform for better outcomes. A growing body of research aims to evaluate how innovative HITs can be co-designed and successfully implemented in mental health services to enhance their provision of care. OBJECTIVE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…As an example, Titov et al [9] have reported success in integrating internet-delivered cognitive behavioral therapy as part of clinical care with a mental health professional in 5 clinics internationally. Unfortunately, far more studies highlight barriers to successful implementations of digital health solutions [10][11][12][13], and further research is required to identify the most effective ways in which to design and implement evidence-based HITs as part of clinical care at scale.…”
Section: Mental Health Service Reformmentioning
confidence: 99%
See 4 more Smart Citations
“…As an example, Titov et al [9] have reported success in integrating internet-delivered cognitive behavioral therapy as part of clinical care with a mental health professional in 5 clinics internationally. Unfortunately, far more studies highlight barriers to successful implementations of digital health solutions [10][11][12][13], and further research is required to identify the most effective ways in which to design and implement evidence-based HITs as part of clinical care at scale.…”
Section: Mental Health Service Reformmentioning
confidence: 99%
“…To that end, Mohr et al [29] highlight the benefits of evaluating the challenges and successes associated with tools such as the InnoWell Platform in targeted clinical settings, such as through the Project Synergy participating services, to iteratively refine and optimize usability, acceptability, and effectiveness to ensure that it meets identified clinical objectives. Therefore, as detailed previously by LaMonica et al [10], we used a mixed methods impact evaluation study, including web-based surveys, semistructured interviews, and workshops, to identify potential barriers to and facilitators of implementation and to evaluate the impact of the InnoWell Platform on the participating mental health services over time, including (1) digital literacy and competence of the service staff in relation to the implementation of the HIT in the service;…”
Section: Impact Evaluationmentioning
confidence: 99%
See 3 more Smart Citations